Neuroablative central lateral thalamotomy for chronic neuropathic pain - Allam, Anthony K.; Larkin, M. Benjamin; McGinnis, John P.; Viswanathan, Ashwin (Frontiers in Pain Research, 2022)
Chronic neuropathic pain refractory to medical management can be debilitating and can seriously affect one's quality of life. The interest of ablative surgery for the treatment or palliation of chronic neuropathic pain, cancer-related or chemotherapy-induced, has grown. Numerous regions along the nociceptive pathways have been prominent targets including the various nuclei of the thalamus. Traditional targets include the medial pulvinar, central median, and posterior complex thalamic nuclei. However, there has been little research regarding the role of the central lateral nucleus. In this paper, we aim to summarize the anatomy, pathophysiology, and patient experiences of the central lateral thalamotomy.